Research on the Social Media Marketing Promoting Brand Loyalty of Local Chinese Cosmetics - Wei, Jiaxiao; Surinta, Olarik; Tirakoat, Suwich (Journal of Ecohumanism, 2024)
The purpose of this study is to explore how social media marketing affects brand loyalty of domestic cosmetics through functional information, entertainment information, interactive information and self-concept. This study adopts quantitative research method, collecting data through questionnaire survey, and using reliability analysis, validity analysis and regression analysis to verify the model. The results show that these four types of information have significant impact on consumers 'cognitive trust and emotional trust, and then affect their attitude loyalty and behavior loyalty. Functional information enhances trust by enhancing product recognition; entertainment information enhances emotional connection by increasing brand interest and attractiveness; interactive information enhances participation and belonging by promoting interaction between consumers and brands; and self-concept plays a mediating role between information type and trust. This study provides theoretical basis and practical guidance for the formulation of social media marketing strategy for domestic cosmetics brands.